Ukraine : democratization, corruption, and the new Russian imperialism - Kuzio, Taras (Santa Barbara, California : Praeger Security International, 2015)
"A definitive contemporary political, economic, and cultural history from a leading international expert, this is the first single-volume work to survey and analyze Soviet and post-Soviet Ukrainian history since 1953 as the basis for understanding the nation today. Ukraine dominated international headlines as the Euromaidan protests engulfed Ukraine in 2013-2014 and Russia invaded the Crimea and the Donbas, igniting a new Cold War. Written from an insider's perspective by the leading expert on Ukraine, this book analyzes key domestic and external developments and provides an understanding as to why the nation's future is central to European security. In contrast with traditional books that survey a millennium of Ukrainian history, author Taras Kuzio provides a contemporary perspective that integrates the late Soviet and post-Soviet eras. The book begins in 1953 when Soviet leader Joseph Stalin died during the Cold War and carries the story to the present day, showing the roots of a complicated transition from communism and the weight of history on its relations with Russia. It then goes on to examine in depth key aspects of Soviet and post-Soviet Ukrainian politics; the drive to independence, Orange Revolution, and Euromaidan protests; national identity; regionalism and separatism; economics; oligarchs; rule of law and corruption; and foreign and military policies. Moving away from a traditional dichotomy of "good pro-Western" and "bad pro-Russian" politicians, this volume presents an original framework for understanding Ukraine's history as a series of historic cycles that represent a competition between mutually exclusive and multiple identities. Regionally diverse contemporary Ukraine is an outgrowth of multiple historical Austrian-Hungarian, Polish, Russian, and especially Soviet legacies, and the book succinctly integrates these influences with post-Soviet Ukraine, determining the manner in which political and business elites and everyday Ukrainians think, act, operate, and relate to the outside world."--
Introduction : seven cycles of Ukrainian history, borders and identities -- Ukraine between Joseph Stalin and Mikhail Gorbachev (1953-1991) -- Independent Ukraine under two Leonids (1991-2004) -- Independent Ukraine between two Viktors (2004-2014) -- Ukrainian dissent, opposition and religion in the USSR -- Politics and parties in independent Ukraine -- Nationality policies in Soviet Ukraine -- Nationality policies, regionalism, and the Crimea in Ukraine -- Economy and energy -- The rule of law and corruption -- Ukrainian oligarchs : the gas lobby, Dnipropetrovsk, and Donetsk -- Foreign policy -- Military and security policy -- Epilogue : history is not destiny.
Vendor-supplied metadata.
Includes bibliographical references (pages 497-586) and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
eBooks on EBSCOhost
Keywords: Ukraine -- Politics and government -- 1991-2014.; Ukraine -- Politics and government -- 1945-1991.; Democratization -- Ukraine; Political corruption -- Ukraine; Ukraine -- Foreign relations -- Russia (Federation); Russia (Federation) -- Foreign relations -- Ukraine; Ukraine -- Politique et gouvernement -- 1991-2014.; Ukraine -- Politique et gouvernement -- 1945-1991.; Démocratisation -- Ukraine; Corruption (Politique) -- Ukraine; Ukraine -- Relations extérieures -- Russie; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Democratization; Diplomatic relations; Political corruption; Politics and government; Russia (Federation); Ukraine; Demokratisering; Politisk korruption; Politiska förhållanden.; Diplomatiska förbindelser.; Politics & government; Since 1945